How can I prove <by induction> the following De Morgan laws are valid for all n >= 2 - ( P(d1) ^ ... ^ P(dn) ) = ( - P(d1) ) v ... v ( - P(dn) ) knowing that -(p^q)=(-p)v(-q) and -((p)v(q))=(-p)^(-q) ? I can use the inductive proof method on algebra/math theorems that have to do with variables, numbers, series, sums, etc. but I don't know what to do with propositions. Help, anyone? I know how to prove the De Morgan laws when it comes to sets, I can also do it by deduction, but I'm just curious as to how you'd go about doing this inductively.